Pemanfaatan Sintaks OpenGL dalam Menggambar Obyek Dua Dimensi - Jackri Hendrik; Tintin Chandra (STMIK TIME, 2015)
Next to nothing area none which get out of requirement of graph. Although initially application in science and engineering need equipments which costly enough. With picture prepare will make easier in reading information and also data compared to by reading data manually in a communications of visual. Which one programming of graphical desain is OpenGL. OpenGL accepted to become one of the standard in computer graphic and in this time have implementation in so many computer system.Early graphical programming is turned into text mode is graphical mode by exploiting function of VGA card. Portability of OpenGL as corps of library conducive to be accessed to to through Ianguage of programming by figuring in OpenGL (library in directory of library Ianguage. In making of object two dimension with OpenGL cannot be direct by calling command which have been provided in library, but require to be done by setting used programming. At programming base on doneeasier visual especially at Visual Microsoft C++ 2005, where there is file of glu*.* placed to 3 folder that is in gl folder include, library, and system32. For coloration at object at OpenGL differ from result of yielded graphic of programming of PACK, because at OpengGL exploit colour of RGB ( Red, Green, Blue), also can be made in the form of colour gradation.